2002
DOI: 10.1179/003258902225001524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silicon addition and process conditions upon α-phase sintering, sinter hardening, and mechanical properties of Fe-1.5Mo powder

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 1 publication
0
24
0
1
Order By: Relevance
“…5C Hanejko et al [16] 1260 7.09 1 1240 sintered and tempered Fe-1.5Mo-3Si-1. 2C Youseffi et al [17] 1250 7.55 0.33 764 sintered and tempered Fe-0.85Mo-6Ni-0. 4C Gething et al [11] 1288 7.50 -943 as-sintered *Estimated from those of 7.05 and 7.30 g Á cm 3 compacts.…”
Section: Ductilitymentioning
confidence: 99%
See 1 more Smart Citation
“…5C Hanejko et al [16] 1260 7.09 1 1240 sintered and tempered Fe-1.5Mo-3Si-1. 2C Youseffi et al [17] 1250 7.55 0.33 764 sintered and tempered Fe-0.85Mo-6Ni-0. 4C Gething et al [11] 1288 7.50 -943 as-sintered *Estimated from those of 7.05 and 7.30 g Á cm 3 compacts.…”
Section: Ductilitymentioning
confidence: 99%
“…As shown in Table IV, these properties are much better than those of the as-sintered or sinter-hardened highstrength PM steels, as reported in recent literature or in the MPIF standards. [1,2,11,[14][15][16][17] Moreover, the 1323 MPa obtained without quenching heat treatment or accelerated cooling is equivalent to the best tensile strength of the quenched and tempered materials registered in the MPIF standards, i.e., FLN2-4405-190HT. [1] These results showed that the Cr addition is very effective in improving the mechanical properties of Ni-containing materials.…”
Section: Strength and Hardnessmentioning
confidence: 99%
“…9 The mechanical properties of UTS of 630 MPa and ETF of y2% found for the sintered hardened material in this study are not as good as those (UTS of 750 MPa and ETF of 2?5%) obtained for Fe-1?5Mo-3Si-1?2C material sintered to 98?8% (7?55 g cm 23 ) relative density. 5 Still, considering the lower relative sintered density (95%) reached in this study for the Fe-2C-2Si material, the mechanical properties are quite satisfactory for hardness levels of ,400 HV. Noteworthy is that even higher hardness levels of y600 HV are achievable for the quenched and tempered alloy.…”
Section: Discussionmentioning
confidence: 78%
“…It was seen that the density of the specimens decreased with increasing Si content. It is known that the addition of Si to iron powder has a shrinkage effect [3] and also reduces the sintered density due to low specific gravity and pressing capability of Si.…”
Section: Resultsmentioning
confidence: 99%
“…Solid solution hardening effect of silicon in the ferrite is higher than the other alloying elements. Youseffi et al [3] noted, however, that silicon has a higher oxygen affinity than copper, nickel and molybdenum.…”
Section: Introductionmentioning
confidence: 95%